2015
DOI: 10.1111/codi.13076
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term anorectal, urinary and sexual dysfunction causing distress after radiotherapy for anal cancer: a Danish multicentre cross‐sectional questionnaire study

Abstract: Distressing long-term anorectal and sexual dysfunction was common after radiotherapy for anal cancer, and morbidity due to urinary dysfunction was moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 55 publications
(101 reference statements)
1
46
0
1
Order By: Relevance
“…Late toxicity from pelvic radiation can include bowel dysfunction (ie, increased stool frequency, fecal incontinence, flatulence, rectal urgency), urinary dysfunction, and sexual dysfunction (ie, impotence, dyspareunia, reduced libido). [145][146][147][148] Anal cancer survivors also report significantly reduced global quality of life, with increased frequency of somatic symptoms including fatigue, dyspnea, pain, and insomnia. 145,149,150 Therefore, survivors of anal cancer should be screened regularly for distress.…”
Section: Survivorshipmentioning
confidence: 99%
“…Late toxicity from pelvic radiation can include bowel dysfunction (ie, increased stool frequency, fecal incontinence, flatulence, rectal urgency), urinary dysfunction, and sexual dysfunction (ie, impotence, dyspareunia, reduced libido). [145][146][147][148] Anal cancer survivors also report significantly reduced global quality of life, with increased frequency of somatic symptoms including fatigue, dyspnea, pain, and insomnia. 145,149,150 Therefore, survivors of anal cancer should be screened regularly for distress.…”
Section: Survivorshipmentioning
confidence: 99%
“…Female rectal and anal cancer survivors have been found to experience substantial sexual difficulties related to vaginal strictures ostomy interference with sexual activity, soiling of personal and bed clothing, bowel and bladder incontinence, pain, and psychological distress (Sun et al, 2016;Sunesen et al, 2015), with prevalence rates of sexual concerns in the range of 19%-62% (DuHamel et al, 2016). Post-mastectomy and lumpectomy, women are faced with scarring, pain, and lost sensation in breast and/or nipple tissue (Falk & Dizon, 2013;Farthmann et al, 2016;Sekse et al, 2010).…”
Section: Effects Of Surgery On Sexual Wellbeingmentioning
confidence: 99%
“…Importantly, sexual dysfunction can become chronic and persist for many years following cancer treatment; similarly, sexual health concerns frequently manifest as late effects of treatment, with severe consequences for women's sexual wellbeing throughout recovery and survivorship (Jensen & Froeding, 2015;Schover, 2014). Women who undergo allogenic haematopoietic stem cell transplantation (HSCT), pelvic radiotherapy, chemoradiotherapy for anal cancer and endocrine therapies (e.g., aromatase inhibitors (AIs) or tamoxifen) are considered to be particularly high-risk for ongoing or late-effect sexual dysfunction (Dyer et al, 2016;Jensen et al, 2004;Schover, 2014;Sunesen et al, 2015). The entrenchment of treatment-related sexual health side-effects (e.g.…”
Section: Physical Impacts Of Cancer Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large studies of various regimes of RT and/or CRT for AC have reported 5-year survival rates of 52-73% [2][3][4][5][6][7][8][9][10][11][12]. Unfortunately, long-term survivors often suffer from severe anorectal dysfunction [13][14][15][16][17][18]. In a study from our unit in Aarhus, Denmark, 31% of patients treated for AC suffered from incontinence to solid stools, 54% had incontinence to liquid stools, 79% had incontinence to gas at least once per month, and 56% had daily episodes of urgency to defecate [14].…”
Section: Introductionmentioning
confidence: 99%